Sleep Disorders and Reproductive Health: Mechanisms, Consequences, and Potential Interventions - Rosa-Bończak, Magdalena; Marta, Patrycja; Huzarski, Filip Maciej; Pawełek, Klaudia Anna; Ferfecka, Gabriela Monika; Ossolińska, Agata; Morawiecka, Natalia; Stolarska, Lucyna; Carlton, Oliver; Kłosowicz, Weronika (Journal of Education, Health and Sport, 2025)
Introduction The role of sleep in maintaining the body’s homeostasis has been the subject of an increasing number of scientific studies, with reproductive health also being dependent on it. Reduced fertility, resulting from the deterioration of reproductive cell quality due to hormonal imbalances, may be a consequence of sleep deprivation. Chronic stress, obesity, and other factors accompanying sleep disturbances can impair the functioning of hormonal axes, ultimately leading to oxidative stress—a metabolic basis for fertility issues. The aim of this study is to analyze the impact of sleep disorders on reproductive health, focusing on the mechanisms, clinical consequences, and potential therapeutic interventions. Materials and Methods This article is based on an analysis of scientific literature concerning the impact of sleep disturbances on reproductive health, utilizing data from databases such as PubMed, Frontiers, and Google Scholar. Studies in fields such as endocrinology, sleep medicine, gynecology, andrology, and psychology were included. Both primary research and systematic reviews, as well as meta-analyses with high methodological quality and statistical significance, were analyzed. This approach provides a comprehensive overview of the relationship between sleep and fertility, considering both biological and psychological mechanisms. Conclusions In both sexes, sleep disturbances can lead to reproductive health problems due to hormonal imbalances, resulting in the deterioration of reproductive cell quality. Factors such as obesity, stress, or shift work further increase the risk of infertility. Recent findings emphasize that mindfulness techniques, cognitive-behavioral therapy, improved sleep hygiene, and even melatonin supplementation may contribute to the success of infertility treatments, including assisted reproductive techniques. It is crucial to raise public awareness about the role of sleep and stress in fertility issues. However, further research is needed to better understand these relationships and develop personalized therapies.